Aspen Plus simulation and optimization of industrial spent caustic wastewater treatment by wet oxidation method - Chandraseagar, S.; Abdul Halim, Abdul Razik; Siti Noredyani, Abdul Rahman; Mohd Aizudin, Abd Aziz (IOP Publishing, 2019)
Spent caustic is a waste generated by petrochemical refineries, which used to eliminate acid components such as hydrogen sulphide (H2S) and mercaptans from the refined product streams. A study was carried out on simulation and optimization of spent caustic wastewater treatment system by using Aspen Plus based on wet air oxidation (WAO) method. WAO method uses air under elevated temperature and pressure to carry out oxidation in the aqueous phase. Process flow diagram (PFD) of WAO method was drawn and relevant input data was keyed in Aspen Plus according to experimental results on WAO. Both results were validated and the results were match each another as the percentage of allowable error between both the results were less than 5 %. After that, optimization was carried out to determine the optimum ratio of spent caustic feed flow rate to air flow rate and operating temperature of the flash separator unit involved in the process. From the optimization results, it can come to a conclusion that 1: 9.2 is the minimum spent caustic feed flow rate to air flow rate ratio and optimum operating temperature of flash separator unit is 140°C in order for maximum flow rate of CH3SSCH3 in offgas stream in this simulation model of spent caustic wastewater treatment system using WAO method.